Love Of Money, Machiavellian dan Idealisme: Bagaimana Pengaruhnya Terhadap Persepsi Etis Akuntan Publik - Junita, Rike Afria; Fauzihardani, Eka (Jurnal Nuansa Karya Akuntansi, 2024)
This study investigated the effects of materialism, marxism, and idealism on public accountants' ethical attitudes in Padang City. the kind of analysis performed in quantitative research to address the previously discussed problems. The Public Accounting Firm in Padang City's auditors were given questionnaires as part of the study's technique of data collection. Because there aren't many public accountants in Padang City, the researchers utilized total sampling as their sample method. The findings of this study demonstrate that Padang City public accountants' judgments of ethics are significantly and negatively impacted by their desire of money. After that, Machiavellian has a bad and considerable influence on Padang city public accountants' moral perspectives. Additionally, idealism significantly and favorably influences how public accountants perceive their ethical obligations. The fact that moral judgments are determined by the variables love of money, machiavellian, and idealism by 20% and other factors are responsible for other variables, which indicates less independence, may be used to explain research limits. Ethical attitudes are influenced by fewer factors than other factors. Other independent factors beyond those employed in this study may be included in future research.